Algorithmic governance, code as law, and the blockchain common: Power relations in the blockchain-based society - Kozak, Krystyna (Frontiers in Blockchain, 2023)
“Code is law” became a buzz term in Web3 and blockchain reality. Despite the term being already used much earlier by Lawrence Lessig in the year 2000 in his book titled “Code and Other Laws of Cyberspace,” when the internet and Web2 were emerging, the rise of smart contracts and complex algorithmic power made the term genuinely resonate with the (idealised) Web3 reality. The entrainment of technological solutionism in the brains of members of society gives an impression that a world governed by algorithms will be a fairer one. However, research has shown that many members of society are not standard statistical representations of the majority and whilst algorithmic governance leaves room for “standard deviation,” individuals that fall outside this standard deviation are, in fact, very disadvantaged. There are numerous research papers as well as popular science books that address the issue of algorithmic bias and unfairness in Web 2. The proponents of blockchain and web3 technology argue that with a DAO-governed, decentralised society, problems of biased algorithmic governance are solved as power and decision-making are decentralised, and members use their governance tokens to collectively decide on the law encoded in the smart contracts that are the ultimate law enforcement apparatus. Web3 promises a shift of power from governments and corporations to people and token holders, arguing it will make a Web3-governed society fairer. This paper is based on decoding this promise and using Althusser’s model of a state apparatus to show how the power relations changed in Web2 and Web3 realities. It shows that Web3 promises of the code becoming the law were already present in the Web2 discourse and discovers a model of an ideological apparatus power struggle between states and Web2 giants. Next, the power relations in the blockchain society are researched, starting from the idealised model of decentralised, token-holder governed power, which regulates the governments and corporations, to a discussion on what the actual power relations and struggles might result from encoding the law in the smart contract. Research shows that in Web3, “code is law” society. There will be power struggles and opposition on a vertical and horizontal level. The vertical struggle is the power enforcement (originally in the hands of the state in Althusser’s (1970) model between the code and individuals, governments and corporations not willing to conform with the code-enforced law or falling outside the standard deviation of statistics-based AI algorithms hence being disadvantaged by the smart contract enforced laws. The horizontal power struggle is based on what Althusser describes as the ideological apparatus. Here, the struggle is based on a fight between individuals (the society), corporations, and the state for code-modifying resources and/or leverage over the governance token holders. Overall, the paper argues and shows that blockchain-based “code is law” reality does not solve the issue of unequal power relations within societies but only as any technological revolution shifts the power relations and power struggles between existing and new actors. Unlike the founder of Polkadot, Gavin Wood states that blockchain, DAOs, smart contracts, and Web3 overall do not result in the new social sphere with revolutionised power relations. Where Web3 is now is much more similar to where Web1 and Web2 were 25–30 years ago—Creating a new space for social interactions and discourse yet being stuck within the same social sphere and uneven power relations that have governed our societies for centuries.